PENGARUH PENERAPAN IFRS KARAKTERISTIK PERUSAHAHAAN DAN KUALITAS AUDITOR TERHADAP AUDIT DELAY - Septiana, Puspa Avinda Dwi; Ratmono, Dwi (Diponegoro Journal of Accounting, 2015)
The value of the timeliness in financial reporting is an important factor for beneficial of the information in the financial statements. Timeliness can be measured by the level of audit delay that calculated by difference between closing date in financial statement until the date of the auditor's report. This study is aimed to examine the influence of IFRS implementation, the company’s characteristics, and the quality of the auditor towards the audit delay. Characteristics of the company used in this study are the company size, the leverage, and the loss announcement.The population used in this study is all of the manufacturing company listed in Indonesia Stock Exchange in 2010, 2011, 2012 and 2013. The writer uses the purposive sampling for the sampling method. The criteria of the company which is used is company must have published audited financial report for four years successively and used rupiah, so that  the number of the sample in this study is 416 data. The analysis technique used in this study is multiple linear regresion.The analysis shows that the company size, leverage and the auditor’s quality  significantly affect the audit delay at different levels of significance. The company size variable affects the audit delay negatively. There are two variables that are not affecting the delay audit, those are the implementation of ifrs, and loss announcement.